The Impact of Ease, Security, and Trust on TikTok Purchase Decisions: A Focus on Generation Z - Putra, Yahya Adhani; Bahri, Mohammad Saiful; Rahmansyah, Ahmad Iskandar (Indonesian Journal of Business Analytics, 2024)
This study examines the impact of Ease of Use, Security, and Trust on the Purchase Decisions of TikTok users, specifically among students from the Faculty of Economics and Business at Universitas Panca Marga. Using a quantitative approach, data were collected from 110 students via a Google Form questionnaire. Analysis through SmartPLS software revealed that Security significantly affects Purchase Decisions, while Ease of Use and Trust showed minimal influence. Findings suggest that TikTok’s data security features play a crucial role in user confidence and purchase intent. This research contributes to understanding how social media platforms influence consumer behavior differently compared to traditional e-commerce sites.